2006
DOI: 10.1590/s1415-52732006000500010
|View full text |Cite
|
Sign up to set email alerts
|

Aleitamento materno: fatores de influência na sua decisão e duração

Abstract: Os autores analisaram diferentes fatores que podem influenciar na decisão das mães de amamentar, na duração da amamentação e as principais razões do desmame. Foram selecionados artigos publicados entre 1990 e 2004 das bases de dados Lilacs, Medline, Scielo, Bireme, utilizando as palavras-chave: desmame e fatores de risco, bem como suas versões em inglês. Alguns fatores, como maternidade precoce, baixo nível educacional e socioeconômico maternos, paridade, atenção do profissional de saúde nas consultas de pré-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
1
133

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(197 citation statements)
references
References 31 publications
5
58
1
133
Order By: Relevance
“…Assim, estudos apontam a importância da participação do pai no sucesso desta prática 4,[6][7][8][9][10] . No entanto, a sociedade brasileira delega ao homem a responsabilidade de provedor financeiro, marginalizando-o a uma participação na criação e cuidados com o filho, no cenário da saúde reprodutiva, nas etapas do ciclo grávido-puerperal e, conseqüentemente, da amamentação.…”
Section: Introductionunclassified
“…Assim, estudos apontam a importância da participação do pai no sucesso desta prática 4,[6][7][8][9][10] . No entanto, a sociedade brasileira delega ao homem a responsabilidade de provedor financeiro, marginalizando-o a uma participação na criação e cuidados com o filho, no cenário da saúde reprodutiva, nas etapas do ciclo grávido-puerperal e, conseqüentemente, da amamentação.…”
Section: Introductionunclassified
“…Among the variables capable of influencing the duration of breastfeeding, the outstanding socioeconomic and demographic conditions include income 3 , schooling 13 , age 16 and mother's work 3 . However, in this study, the variables corresponding to the age, schooling and employment status of the mothers had no statistically significant association with the length of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…The duration and prevalence of breastfeeding has been less in socioeconomically disadvantaged populations 3 , where the negative consequences of the lack of breastfeeding may be even greater. Children who did not receive maternal milk effectively in the first years of life have greater risk of developing infections, in addition to increased risk of morbidity and mortality from pneumonia and diarrhea 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Studies have indicated that the participation of the father is important to the success of this practice. 4,[6][7][8][9][10] However, Brazilian society delegates responsibility to the man for being the financial provider, marginalizing him and excluding him from participating in the upbringing and care of children, in the context of reproductive health, during the pregnancy-childcare stages of the cycle and, consequently, from participating in breastfeeding. It is as though all of this, almost exclusively, belongs to the woman's world.…”
Section: Introductionmentioning
confidence: 99%